Impact of the Shadow Economy on Tax Buoyancy in Central Java - Fazriel Alfathan; Agus Arifin (Economics Development Analysis Journal, 2025)
Taxation plays a strategic role as the primary source of government revenue, supporting fiscal stability and sustainable economic growth. In this context, tax buoyancy serves as an important indicator for evaluating the responsiveness of tax revenues to economic growth. Despite its substantial contribution to regional income, Central Java exhibits the lowest level of tax buoyancy among provinces on the island of Java, indicating the presence of unrealized fiscal potential. This study examines the effect of the shadow economy on tax buoyancy using a labor-based approach and panel data regression with a Fixed Effects Model. The analysis utilizes secondary data from the Directorate General of Fiscal Balance (Direktorat Jenderal Perimbangan Keuangan/DJPK) and Statistics Indonesia (BPS) for the period 2016–2022. The independent variables include population, investment, and the shadow economy. The results indicate that population has a negative effect on tax buoyancy, while investment shows no statistically significant effect. In contrast, the shadow economy exerts a significant positive influence on tax buoyancy. The novelty of this research lies in its application of a labor-based approach to capture the dynamics of the shadow economy within a tax buoyancy framework. These findings highlight the importance of policy strategies aimed at formalizing the informal sector through tax incentives, regulatory simplification, and improvements in business licensing systems in order to enhance the sustainability of tax revenues.